Effects of the flue gas treatment of incinerator plants on sub-micron particle concentrations at the stack. (1st January 2020) - Stabile, L.; Scungio, M.; Frattolillo, A.; Buonanno, G.
Highlights: Sub-micron particle emissions of incinerator plants. Particle number concentrations and distributions measurements. Effects of the fabric filter bag age on the emission of sub-micron particles. Effects of the SCR system on the emission of sub-micron particle of incinerators. Flue-gas treatment removal efficiency of sub-micron particles >99.99%. Abstract: The paper is focused on the emission of sub-micron particles from incinerator plants characterized by different treatment sections. In particular, measurement of particle number concentrations and distributions in different sampling points of the flue-gas treatment sections, and/or over several years, allowed to detect, for the very first time through in-field tests, the effect of the age of the fabric filter bags and of the SCR system on the emission of sub-micron particles. In fact, tests showed that the age of the fabric filter bags can affect the particle number concentrations at the stack: indeed, for older bags higher concentrations at the stack were measured likely due to the filter cleaning process. Concerning the effect of the SCR system, the natural gas combustion performed in the SCR system leads to an increase of sub-micron particle concentrations at the stack with respect to the values measured after the filtration section.